Under the microscope science tools - Clark, John Owen Edward (Danbury, CT Grolier Educational, 2003)
Describes the fundamental units and measuring devices that scientists use to bring systematic order to the world around them
v. 1. Length and distance -- v. 2. Measuring time -- v. 3. Force and pressure -- v. 4. Electrical measurement -- v. 5. Using visible light -- v. 6. Using invisible light -- v. 7. Using sound -- v. 8. Scientific analysis -- v. 9. Scientific classification
Hurg
5 8 18
Keywords: Measuring instruments -- Juvenile literature; Measuring instruments; Scientific apparatus and instruments -- Juvenile literature; Scientific apparatus and instruments; Weights and measures -- Juvenile literature; Weights and measures